Examining the Effect of Metformin on Cell Death Mechanisms in Relation to Hippo Signaling in MDA-MB-231 Breast Cancer Cells - RENCÜZOĞULLARI, ÖZGE; SONALP, ZEYNEP GÜLŞAH (Si̇vas Cumhuri̇yet Üni̇versi̇tesi̇, Fen Fakültesi̇, 2024)
Breast cancer is one of the most common cancer types in women in the world and our country. Antitumorigenic activity is achieved with various therapeutic drugs by directly suppressing the constantly active PI3K/Akt/mTOR signaling pathway or enabling AMPK activation. AMPK, a positive regulator of autophagy, ensures the induction of autophagy by suppressing the Akt/mTOR pathway. Metformin, an anti-diabetic drug, achieves its anti-tumorigenic effect by activating AMPK. Deregulation of the Hippo signaling pathway is a new therapeutic target because it causes cancer cells to become aggressive and evade cell death mechanisms. The study aims to reveal the effects of metformin treatment on Hippo signaling pathway activity on apoptosis and autophagy, depending on drug treatment in MDA-MB-231 breast cancer cells. Metformin decreased the cell viability through induction of mitochondria membrane potential loss in dose and time dependent manner in MDA-MB-231 cells. The colony forming potential of the MDA-MB-231 cells were suppressed by 10 mM metformin treatment which was induced apoptotic cell death and autophagy by increasing Bim, Bad, Bak and cleavage of caspase 3, 9, PARP and Beclin1, Atg5 and Atg7. Moreover, Hippo signaling related protein levels showed remarkable increase due to metformin treatment. It was shown that metformin treatment increased the activity of the hippo signaling pathway, resulting in the induction of apoptosis and autophagy.
Keywords: Breast Cancer; Metformin; Hippo Signaling; Apoptosis; Autophagy